(untitled) (Bangladesh Critical Care Journal, 2024)
Empagliflozin-induced Euglycemic Diabetic Ketoacidosis (EDKA) is a life-threatening metabolic emergency of Diabetes Mellitus. It is characterized by metabolic acidosis (i.e., pH <7.3 and Serum bicarbonate <15mEq/dl) with an increased anion gap, ketonemia and relatively normal serum glucose level. EDKA resembles Diabetic Keto Acidosis (DKA) but does not exhibit the typical high blood sugar levels. In EDKA, blood glucose is usually below 200 mg/dL. This condition is a diagnostic challenge as euglycemia masks the underlying diabetic ketoacidosis. Here we present a case of Empagliflozin-induced Euglycemic Diabetic Ketoacidosis presented with palpitation and several episodes of vomiting. The aim of this article is to create awareness among clinicians to consider this diagnosis in the differential, especially in the patients taking SGLT-2 inhibitors. Bangladesh Crit Care J September 2024; 12 (2): 172-174